Construction forSmart Cleaning Management using IoT Based on Digital Signage - Byeongtae Ahn, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In particular, changes in digital signage technology are developing in various ways due to the development of advanced convergence technologies. With the development of convergence technologies, digital signage has been constructed to provide information through a structured structure between each component in order to develop in a form that can deliver information in response to environmental changes rather than user input. This paper developed a system that outputs and services various contents together with industrial facility inspection and management by using wireless communication Bluetooth in a display device equipped with an operating system